Effects of Vibrio harveyi infection on serum biochemical parameters and expression profiles of interleukin-17 (IL-17) / interleukin-17 receptor (IL-17R) genes in spotted sea bass. (September 2020) - Mao, Xuebin; Tian, Yuan; Wen, Haishen; Liu, Yang; Sun, Yalong; Yanglang, Arat; Li, Yun
Abstract: Vibrio harveyi is regarded as serious pathogen for marine fishes. To evaluate the physiological responses of spotted sea bass ( Lateolabrax maculatus ) after V. harveyi infection, four biochemical biomarkers including alanine amino transferase (ALT), albumin (ALB), total protein (TP) and glucose (GLU) were measured in serum. Our results showed that V. harveyi infection significantly influenced the concentration of ALT, ALB and GLU. Additionally, five interleukin-17 (IL-17) and five IL-17 receptors (IL-17R) genes were identified in spotted sea bass and their gene structures were characterized. Furthermore, the expression patterns of IL-17 and IL-17R genes were determined by qPCR in liver, intestine, spleen and head kidney after V. harveyi infection. All IL-17 and IL-17R genes exhibited time- and tissue-dependent expressions. Several tested genes were dramatically induced by V. harveyi treatment, particularly IL-17A/F1 in liver and head kidney, IL-17A/F2 in head kidney, IL-17RC in spleen with more than 10-fold increases, which suggested their potential essential roles against bacterial infection. Highlights: V. harveyi infection significantly influenced the concentration of ALT, ALB and GLU. Five interleukin-17 (IL-17) and five IL-17 receptors (IL-17R) genes were characterized in spotted sea bass. The expressions of IL-17A/F1, IL-17A/F2 and IL-17RC genes were dramatically induced after V. harveyi infection.